Sports tutors’ perceptions of primary school physical education: A contextual analysis - D’Isanto, Tiziana; D’Elia, Francesca; Aliberti, Sara; Raiola, Gaetano (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The 2022 Italian budget law introduced two weekly physical education (PE) hours in IV and V primary classes with a specialist teacher. Ahead of this, the "Active Kids in School" (ASK) project, led by a sports tutor alongside the generalist teacher, ran in IV and V classes in 2021/2022. The aim of this study was to analyze the current contextual situation related to the teaching of PE in primary school, through the perceptions of the ASK project’s sports tutors, potential PE teachers with master’s degree in exercise and sport sciences. A descriptive correlational study design was implemented. An ad hoc questionnaire, focused on participants’ characteristics, tutors’ perceptions on their teaching, perceived competence and work satisfaction, and obstacles to PE, was administered to 48 sports tutors (26±2.4 years), recruited through convenience sampling. The results showed a critical situation related to PE teaching in primary school, mainly due to the training gaps of tutors in sports, inclusive strategies and classroom group management, and the lack of gyms and sports equipment. Significant correlations emerged between tutors’ age and PE training adequacy (p=.007; r =.38), tutors’ age and perception of work satisfaction (p=.001; r =.44), PE training adequacy and work satisfaction (p=.000; r =.85). This evidence should be considered by authorities managing the system-wide adoption of legislative innovation, particularly teacher-training universities.